A vesico-peritoneal fistula in a patient with history of diverticulitis-related colovesical fistula repair: a case report - Garza, Alberto Riojas; de Elguea Lizárraga, José Ignacio Ortiz; Müller, Giovanna Arteaga; Orozco Saldivar, Miguel A.; Salgado Cruz, Luis E. (International Surgery Journal, 2020)
A vesico-peritoneal fistula is an epithelialized communication between the peritoneal cavity and the urinary bladder. It is a rare entity scarcely reported in medical literature. High index of suspicion is needed for diagnosis and treatment. Here we expose the case of a vesico-peritoneal fistula presenting with chronic abdominal pain 4 years after sigmoidectomy. A 38-year-old male presented with lower quadrant abdominal pain. He had history of sigmoidectomy with colorectal anastomosis and bladder repair due to diverticular disease-related colovesical fistula 5 years prior to admission. Elevated serum creatinine levels and oliguria were documented. Intraperitoneal free fluid was found by computed tomography (CT) scan. Percutaneous drainage was performed, and laboratory test showed elevated peritoneal creatinine levels. CT-Cystography revealed a vesico-peritoneal fistula. Dissection of fistulous tract and primary closure of bladder defect was achieved. Vesico-peritoneal fistulas have been described as surgical procedure complications with a variable postoperative time of presentation. Low index of suspicion led to delayed diagnosis, finally suspected by intraperitoneal fluid analysis and confirmed by cystography. Intraperitoneal reabsorption of urine elevated serum creatinine levels mimicking renal failure. Management ranges from conservative to surgical procedures, in this case fistulous tract dissection and primary bladder closure was accomplished. Vesico-peritoneal fistulas are rarely reported. Common clinical findings include chronic abdominal pain and free intraperitoneal fluid. Misdiagnosis of acute renal failure is frequent due to elevated serum creatinine levels and oliguria. Laparoscopic dissection of fistulous tract and primary closure of bladder defect is a safe option as treatment of this condition.